Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 786 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Antidorcas marsupialis (Zimmermann, 1780)" ] } The dataset includes 786 records from 49 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002018-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences